Nuclear oligo hashing improves differential analysis of single-cell RNA-seq - Hyeon-Jin Kim; Greg Booth; Lauren Saunders; Sanjay Srivatsan; José L. McFaline-Figueroa; Cole Trapnell (Nature Communications, 2022)
Using spike-in controls with current single cell RNA-seq platforms remains a challenge. Here, the authors use a mixture of short, unmodified DNA oligos as a normalization standard for sci-RNAseq to improve the detection of global transcriptome changes.